FAKTA CERITA DAN TEMA DALAM NOVEL DIKTA DAN HUKUM KARYA DHIA'AN FARAH - Niza Alnur Ayyun; Marwati; La Tike (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2024)
This research is a study of literary works (novels) which aims to describe a structure in the story in detail and in detail. This research discusses story facts and themes in the novel Dikta and Hukum by Dhia'an Farah. The aim of this research is to describe story facts and themes in the novel Dikta and Hukum by Dhia'an Farah. This research is library research. The method used in this research is descriptive qualitative. This research data is written data, namely all story elements related to story facts and themes in the novel Dikta and Hukum by Dhia'an Farah. The data source in this research is the novel entitled Dikta and Hukum by Dhia'an Farah, published by Asoka Aksara X Loveable (2021). The data collection technique in this research is using intensive reading techniques and analytical reading techniques. Furthermore, this research will be analyzed using a structural approach. The results of this research show that the novel Dikta and Hukum by Dhia'an Farah has 2 main characters and 15 additional characters. The flow used is a mixed flow because apart from using a forward flow there is also a backward flow in each event. The settings in the novel Dikta and Hukum by Dhia'an Farah are Nadhira's house, class, school canteen, law faculty, Dikta's house, library, parking lot, faculty canteen, hospital, bus stop, cafe, Jodi boarding house, Sentul rest area , Secretary of HIMA, School Rooftop, Beach and cemetery. The time setting in the novel Dikta and Hukum by Dhia'an Farah is morning, afternoon, afternoon and evening. The social setting in the novel Dikta and Hukum by Dhia'an Farah is thick with beliefs, traditions and language.